Artocarpus lacucha Extract and Oxyresveratrol Inhibit Glucose Transporters in Human Intestinal Caco-2 Cells - Wongon, Matusorn; Limpeanchob, Nanteetip (Planta Medica, 2021)
Reduction of intestinal glucose absorption might result from either delayed carbohydrate digestion or blockage of glucose transporters. Previously, oxyresveratrol was shown to inhibit α-glucosidase, but its effect on glucose transporters has not been explored. The present study aimed to assess oxyresveratrol-induced inhibition of the facilitative glucose transporter 2 and the active sodium-dependent glucose transporter 1. An aqueous extract of Artocarpus lacucha, Puag Haad, which is oxyresveratrol-enriched, was also investigated. Glucose transport was measured by uptake into Caco-2 cells through either glucose transporter 2 or sodium-dependent glucose transporter 1 according to the culture conditions. Oxyresveratrol (40 to 800 µM) dose-dependently reduced glucose transport, which appeared to inhibit both glucose transporter 2 and sodium-dependent glucose transporter 1. Puag Haad at similar concentrations also inhibited these transporters but with greater efficacy. Oxyresveratrol and Puag Haad could help reduce postprandial hyperglycemic peaks, which are considered to be most damaging in diabetics.
Keywords: Artocarpus lacucha; Moraceae; oxyresveratrol; glucose transporter; Caco-2 cells